Modeling Pre Development Profitability of Trade Mall Projects on Developer Competitiveness Performance with Supply & Demand Dynamics - Lia Eka Prianti; Akhmad Taufik Aditama (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
The Trade Mall project as part of the property business, is project with the highest market absorption rate among other commercial property projects such as apartments, hotels, housing, offices, and industry. The purpose of this study is to evaluate the pre development strategy of trade mall projects in order to increase the profitability and competitiveness of developers in major cities and to identify the variables that determine the profitability of Trade Mall project pre development, develop a dynamic system model that can illustrate the influence of supply and demand for Trade Mall project development on the competitiveness of developers, and make recommendations for corrective actions to address the causes of the decline in profitability and competitiveness of developers. The research methods used archival analysis and surveys. The data obtained is then analyzed using statistical analysis and system dynamics. The results of the study show that there two main factors that affect the level of project profitability, namely the selling price and sales level, and the Trade Mall growth gap obtained from supply & demand simulations. Recommendations for corrective actions were also made to address the causes of the decline in profitability and competitiveness of developers.The results of study can basis for Trade Mall project developers to make supply and demand projections in developing the Trade Mall project.